Genetic diversity of non-Saccharomyces yeasts associated with spontaneous fermentation of Cabernet Sauvignon wines from Ningxia, China - Li, Ruirui; Feng, Danping; Wang, Hui; Zhang, Zhong; Li, Na; Sun, Yue (Frontiers in Microbiology, 2023)
The organoleptic profile and quality of wine are affected by the presence of different non-Saccharomyces species and strains. Therefore, the identification and characterization of non-Saccharomyces yeasts are the first step to understand their function, and to develop a better strain selection program for winemaking. This study investigated the biodiversity of non-Saccharomyces yeasts associated with spontaneous fermentation of Cabernet Sauvignon wines from five sub-regions (Shi Zuishan, Yinchuan, Yu Quanying, Qing Tongxia and Hong Sibu) in Ningxia, China. Yeast species were identified by sequencing the 26S rRNA D1/D2 region, and strains at the subspecies level were discriminated using tandem repeat-tRNA (TRtRNA) PCR analysis. A total of 524 yeast colonies were isolated, and 19 non-Saccharomyces yeast species belonging to 10 genera were identified, including Aureobasidium pullulans, Cryptococcus albidus, Cryptococcus sp., C. flavescens, C. terrestris, C. magnus, Cystofilobasidium ferigula, Candida zemplinina, Filobasidium magnum, Filobasidium sp., F. elegans, Hanseniaspora uvarum, Metschnikowia pimensis, M. pulcherrima, Naganishia albida, Pichia kluyveri, P. kudriavzevii, Rhodotorula glutinis and R. graminis. Hanseniaspora uvarum, C. zemplinina, and M. pulcherrima were the three most dominated species, while other non-Saccharomyces species were only present in the early stage of spontaneous fermentations at different levels. Further, for the yeast discrimination at strain level, 34 profiles were obtained by amplification with primer pairs TtRNASC/5CAG, while 40 profiles were obtained with primer pairs TtRNASC/ISSR-MB. This study explored the diversity of non-Saccharomyces species in Ningxia, China, and made an important contribution of genetic resources for further strain development.